Histo-architectural changes of intestinal morphology in Zebra fish (Danio rerio) exposed to Sumithion - Ahmed, Sk Istiaque; Ahmmed, Mirja Kaizer; Ghosh, Subrata Kumar; Islam, Md Moudud; Shahjahan, Md (Research in Agriculture Livestock and Fisheries, 2015)
Organophosphorous pesticide sumithion, the O, O Dimethyl O- (3-methyl-4-nitrophenyl), is a widely used pesticide in agricultural land and in aquaculture to control some harmful pests. A study was conducted in laboratory condition with aquaria (36 inch × 10 inch × 12 inch) to evaluate the effects of sumithion on histo-architecture of intestine in zebrafish (Danio rerio). The experiment was carried out with three treatments (T1: 0.5 ppm, T2: 1.0 ppm, T3: 2.0 ppm) and a control (T0: 0ppm), each having three replications. Zebra fishes (Danio rerio) (4±1cm and 0.9±0.2g) were stocked for the experiment and sacrificed after 7 days of exposure of sumithion. During the study period, the temperature was almost constant (21- 22OC) but dissolved oxygen, pH and total alkalinity values were tended to decrease with the increase in concentrations of test chemicals. The histo-architectural changes in intestine suggested that the intestinal epithelial cells, lumen, villi and intestinal folding were varied significantly (P<0.05) in treatment groups rather than the control groups (T0). Disappeared mucosa (DM) along with abnormal lumen (AL) were found in case of T1, while destructed intestinal villi (DV), sloughing of superficial epidermal cells (SEC) and uneven intestinal folding (UF) were found in T2 and T3. The obtained result supports the toxic potentiality of sumithion. Therefore, the use of sumithion must be evaluated carefully in agriculture and aquaculture. Res. Agric., Livest. Fish.2(3): 499-506, December 2015